The Immunomodulatory Role of Adjuvants in Vaccines Formulated with the Recombinant Antigens Ov-103 and Ov-RAL-2 against Onchocerca volvulus in Mice - Hess, Jessica A. (PLoS Negl Trop Dis, 2016)
BACKGROUND: In some regions in Africa, elimination of onchocerciasis may be possible with mass drug administration, although there is concern based on several factors that onchocerciasis cannot be eliminated solely through this approach. A vaccine against Onchocerca volvulus would provide a critical tool for the ultimate elimination of this infection. Previous studies have demonstrated that immunization of mice with Ov-103 and Ov-RAL-2, when formulated with alum, induced protective immunity. It was hypothesized that the levels of protective immunity induced with the two recombinant antigens formulated with alum would be improved by formulation with other adjuvants known to enhance different types of antigen-specific immune responses. METHODOLOGY/ PRINCIPAL FINDINGS: Immunizing mice with Ov-103 and Ov-RAL-2 in conjunction with alum, Advax 2 and MF59 induced significant levels of larval killing and host protection. The immune response was biased towards Th2 with all three of the adjuvants, with IgG1 the dominant antibody. Improved larval killing and host protection was observed in mice immunized with co-administered Ov-103 and Ov-RAL-2 in conjunction with each of the three adjuvants as compared to single immunizations. Antigen–specific antibody titers were significantly increased in mice immunized concurrently with the two antigens. Based on chemokine levels, it appears that neutrophils and eosinophils participate in the protective immune response induced by Ov-103, and macrophages and neutrophils participate in immunity induced by Ov-RAL-2. CONCLUSIONS/SIGNIFICANCE: The mechanism of protective immunity induced by Ov-103 and Ov-RAL-2, with the adjuvants alum, Advax 2 and MF59, appears to be multifactorial with roles for cytokines, chemokines, antibody and specific effector cells. The vaccines developed in this study have the potential of reducing the morbidity associated with onchocerciasis in humans.